SEPARATION OF SAVORY FRACTION FROM AUTOLYSATE OF KIDNEY BEAN (Phaseolus vulgaris L.) FERMENTED BY Rhizopus sp-PL19 THROUGH CROSS-FLOW MICROFILTRATION (CFMF) MEMBRANE MODULE - Aspiyanto Aspiyanto; Agustine Susilowati; Yati Maryati (Jurnal Kimia Terapan Indonesia, 2014)
Separation of savory fraction from autolysate of kidney bean (Phaseolus vulgaris L.) fermented by Rhizopus sp.-PL19 as potential seasoning agent was performed using cross-flow microfiltration (CFMF) technique in module scale. The goal of this experiment was to find out the effect of pressure and time on performance of MF membrane, and compositions of retentate and permeate. The result of experiment showed that separation and/or purification using CFMF technique gave permeate as savory fraction with better clearness and sharper aroma than retentate, but retentate had better composition than permeate. During separation increased total protein, dissolved protein and salt concentrations, but decreased total solid, reducing sugar and fat concentrations in permeate at pressure of 2 and 4 bar. Based on N-Amino concentration in permeate, the optimum condition of separation was reached at pump motor frequency of 10 Hz and room temperature with  pressure of 2 and 4 bar for 10 minutes. This condition produced permeate with fluxes of 51.11 and 52.55 L/m2.hour, and concentrations of N-Amino of 5.50 and 9.80 mg/mL, dissolved protein of 1.01 and 0.97 mg/mL, total protein of 4.85 and 12.10 % (dry weight), reducing sugar of 55.75 and 53.75 mg/mL, salt of 1.16 and 1.06 %, fat of 0.41 and 0.65 %, and total solids of 7.82 and 6.35 %, respectively. Keywords : Autolysate, kidney bean (Phaseolus vulgaris L.), Rhizopus sp.-PL19, cross-flow microfiltration (CFMF), permeate, retentate.  Pemisahan fraksi gurih dari autolisat kacang merah (Phaseolus vulgaris L.) terfermentasi oleh Rhizopus sp.-PL19 sebagai bahan seasoning potensial dilakukan menggunakan teknik mikrofiltrasi cross-flow (MFCF) pada modul.Penelitian bertujuan untuk mencari pengaruh tekanan dan waktu pemisahan terhadap kinerja membran mikrofiltrasi (MF) dan komposisi dalam retentat dan permeat. Hasil penelitian menunjukan bahwa pemisahan dan/atau pemurnian menggunakan teknik MFCF memberikan permeat sebagai fraksi gurih savory dengan kejernihan lebih baik dan aroma lebih tajam daripada retentat, tetapi retentat memiliki komposisi lebih baik daripada permeat. Pemisahan dengan waktu lama menaikkan konsentrasi total protein, protein terlarut dan garam, namun mengurangi konsentrasi total padatan, gula pereduksi dan lemak dalam permeat pada tekanan 2 dan 4 bar. Berdasarkan konsentrasi N-Amino dalam permeat, kondisi optimum pada pemisahan dicapai dibawah frekuensi motor pompa 10 Hz dan suhu ruang dengan tekanan 2 dan 4 bar selama 10 menit. Kondisi ini menghasilkan permeat dengan fluks masing-masing 51,11 dan 52,55 L/m2.jam serta konsentrasi N-Amino of 5,50 dan 9,80 mg/mL, protein terlarut 1,01 dan 0,97 mg/mL, total protein  4,85 dan 12,10 % (berat kering), gula pereduksi 55,75 dan 53,75 mg/mL, garam 1,16 dan 1,06 %, lemak 0,41 dan 0,65 % serta total padatan 7,82 dan 6,35 %. Kata kunci : Autolisat, kacang merah (Phaseolus vulgaris L.), Rhizopus sp.-PL19, mikrofiltrasi cross-flow (CFMF), permeat, retentat.